Labor Force Participation in Chile : Recent Trends, Drivers, and Prospects - Blagrave, Patrick (IMF Working Papers; Working Paper ;, 2017)
Gains in labor force participation rates in Chile have slowed in recent years. We examine their determinants using a cohort-model analysis. Allowing for both age- and cohort-specific effects in the context of a seemingly unrelated regression equations (SURE) approach, we find that age factors play an important role in determining participation decisions, especially for males. For females, we find that strong positive time trends dominate the downward pressure from demographics, although those trends have recently dissipated. In addition, we find that both cohort effects and the business cycle shape participation decisions. Using our cohort-based analysis, we construct projections of participation rates, which suggest population aging will put downward pressure on labor inputs, and thus potential output, in coming years. Further increases in female labor force participation-supported by policies- could more than offset the downward pressure from demographics.